Effects of policy and educational interventions intended to reduce difficulties in literacy skills in grade 1. (June 2019) - Ecalle, Jean; Gomes, Christophe; Auphan, Pauline; Cros, Laurent; Magnan, Annie
Highlights: Two large-scale studies were conducted in zones with specific educational needs. The reduction of the class size had an effect on reading and spelling. Targeted interventions in favor of low achievers had an effect on literacy skills. Effect sizes that vary from .12 to .32 are found in large samples. Abstract: In two large-scale studies, the effects of policy and educational interventions on literacy skills were examined in children schooled in zones with specific educational needs. To calculate the potential effects of such interventions, treatment-effects estimators with nearest neighbor matching were used. In Study 1 with policy intervention ( N = 1095), children in experimental group (Exp) were assigned to small classes (12 pupils) and others in control group (Cont) to normal-sized classes (20–25 pupils). At the end of Grade 1, the effect sizes in favor of Exp were .14 and .22 in word reading and spelling. In Study 2 with educational interventions ( N = 2803), children in Exp benefit from an evidence-based practice, i.e. a code-focused intervention (phonology, letter knowledge, decoding and fluency) developed by the Association Agir pour l'Ecole (Act for School) and conducted by teachers in small groups for children with low performance at the beginning of Grade 1. The effect sizes of interventions in various literacy skills were from .12 to .32. This set of results obtained in France is in accordance with those described in other countries. To conclude, a double intervention with small classes and targeted educational approaches could be one of the best ways of reducing inequalities during learning to read.